Change Detection Methods Using Band Ratio and Raster to VectorTransform - Al-Hassany, Gheidaa (Iraqi Journal of Science, 2024)
LandSat Satellite ETM+ images have been analyzed to detect changes inEuphrates river boundaries area at the middle of Iraqi country from the year 1990 tothe year 2001. Changes are determined by applying the rationing method on thebands 3 and 5 then using Raster to Vector (R V)Transform method .GIS 9.1 programis used to apply the rationing method and Raster to Vector (R V)Transformtechnique then determined the results (changes in boundaries area were calculated).